PAPILLARY CARCINOMA OF THE THYROGLOSSAL DUCT CYST: A CASE REPORT - Duzhiy, Ihor; Kononenko, Mykola; Moskalenko, Yuliia; Zhukova, Kseniia (Eastern Ukrainian Medical Journal, 2023)
Introduction. Thyroglossal duct cysts (TGDCs) can be diagnosed at any age. They are most common in women aged 30–40. Cysts can become malignant in 1% of patients. As a result, a very rare tumor – TGDC carcinoma – develops. Some oncologists believe it is sufficient to perform surgery using the Sistrunk procedure. Other scientists insist on performing the Sistrunk procedure followed by thyroidectomy, lymph node dissection, and radioactive iodine ablation. In this report, we would like to share our successful experience in treating a patient with papillary carcinoma of PCOS. Case report. A 47-year-old woman had persistent midline neck swelling for three years. This lesion was completely asymptomatic. The patient had no cases of head and neck irradiation or a family history of thyroid gland diseases. Physical examination revealed a solid, movable, smooth mass measuring 6.0 × 5.0 × 4.0 cm on the anterior surface of the neck. The thyroid gland was of normal size, without nodules. Lymph nodes of the neck were not enlargement. During sticking out the tongue and swallowing, the tumor moved upwards. Neck ultrasound, CT scan, and fine-needle aspiration biopsy confirmed the presence of TGDC papillary carcinoma. All laboratory results, including thyroid hormones, were within normal ranges. The patient underwent the Sistrunk procedure, total thyroidectomy with central lymph node dissection, radioactive iodine ablation, and suppression of thyroid function with levothyroxine. The patient’s follow-up period has been currently 110 months. There were no signs of relapse. Discussion. The etiology of the malignant transformation of the TGDC remains unknown. One of the main theories is the spontaneous development of ectopic thyroid tissue located in the cyst walls. Ultrasound, CT, and MRI are considered sufficiently informative methods. A fine-needle aspiration biopsy confirms TGDC carcinoma in 53% of patients before surgery. Virtually all patients with TGDC carcinomas undergo the Sistrunk procedure. In addition, some of them perform a total thyroidectomy. Criteria for total thyroidectomy are age older than 45 years, history of neck irradiation, tumor size greater than 4 cm, presence of regional metastases, and thyroid gland dysfunction. Postoperative radioiodine ablation and suppressive levothyroxine therapy are considered the best treatment before the start of the follow-up period. Conclusions. The treatment of patients with TGDC carcinomas should be personalized. Determining criteria should be the patient’s age, gender, condition of the thyroid gland and regional lymph nodes, size of the primary tumor, resection margins, invasion of the tumor into the surrounding tissues, and family history of thyroid diseases.